Kajian Sifat Organoleptik dan Zat Gizi Formula Roti Tawar Subtitusi Tepung Labu Kuning sebagai Makanan Selingan pada Anak Sekolah Dasar - Hidayati, Nurgina; Dewi, AASP Chandra; Abdi, Lalu Khairul; Sofiyatin, Reni (Student Journal Nutrition (SJ Nutrition), 2023)
Background: White bread is a food product made from a mixture of simple ingredients such as wheat flour, granulated sugar, eggs, margarine, yeast. To increase the nutritional value of white bread, white bread products have been developed to substitute pumpkin flour which are high in protein and rich in dietary fiber, anti-oxidants, minerals, vitamin A, vitamin C and vitamin E for elementary school children.  Research Objectives: To identify the organoleptic properties (color, aroma, taste and texture) and nutritional content (energy, protein, fat, carbohydrates, fiber and vitamin A) in selected substitute white bread as a snack product for elementary school children.  Research Method: This research uses an experimental or experimental method with a Completely Randomized Design (CRD). Organoleptic properties were tested using the hedonic test method with 15 panelists.  Results: The results of the organoleptic study of white bread products substituted with pumpkin flour revealed that the best treatment was t1 with 10% pumpkin flour substitute. The nutritional value of 1 portion weighing 50 grams of yellow pumpkin bread is 225.05 kcal energy, 5.3 grams protein, 5.7 grams fat, 41.75 grams carbohydrates, 0.18 grams fiber, 61.66 mg vitamin A.  Conclusion: Pumpkin white bread with the best treatment is t1 (10% substitution of pumpkin flour for total wheat flour). You get a yellow color with a distinctive aroma of white bread and pumpkin with a slightly sweet and savory taste and a soft texture. The nutritional value of 1 portion weighing 50 grams of yellow pumpkin bread is 225.05 kcal energy, 5.3 grams protein, 5.7 grams fat, 41.75 grams carbohydrates, 0.18 grams fiber, 61.66 mg vitamin A.